Gamification as a methodology to enhance analytical and sustainable engagement on social media - Paula Gil Ruiz (Springer, 2024)
Abstract This research examines the impact of gamification on the development of critical thinking skills to counter misinformation, focusing specifically on students' roles as developers of educational software. Involving 107 university students, this study employs an experimental pretest-posttest methodology. An educational Escape Room was implemented, and its influence on critical and digital competencies was scrutinized. The procedure comprised three stages: pretest measurement, formative intervention, and posttest evaluation. A comparative analysis of the scores for the questions highlights a pressing need to enhance media and digital literacy. The findings reveal a predominance of responses indicating improvements in source verification and fact-checking. However, no significant differences were observed in the pre and post responses (0.607 > 0.05), leading to the conclusion that the implementation of a technological training program does not significantly contribute to acquiring skills for identifying falsehoods and deceptions on the internet. In conclusion, the study underscores the necessity to develop effective strategies to address misinformation and recognizes gamification as a motivating educational tool.